A Novel Technique to Estimate Biological Parameters in an Epidemiology Problem - Benedito, Antone dos Santos [UNESP]; Pio dos Santos, Fernando Luiz [UNESP]; Rojas, I; Joya, G.; Catala, A. (Springer, 2017)
In this paper, we describe a study of a parameter estimation technique to estimate a set of unknown biological parameters of a nonlinear dynamic model of dengue. We also explore a Levenberg-Marquardt (LM) algorithm to minimize the cost function. A classical mathematical model describes the dynamics of mosquitoes in water and winged phases, where the data are available. The main interest is to fit the model to the data taking into account the parameters estimated. Numerical simulations were performed and results showed the robustness of LM in estimating the important parameters in the dengue disease problem.
Keywords: Computational population dynamics; Ordinary differential system; Aedes; Dengue